High fat diet blunts the effects of leptin on ventilation and on carotid body activity. (15th January 2018) - Ribeiro, Maria J.; Sacramento, Joana F.; Gallego‐Martin, Teresa; Olea, Elena; Melo, Bernardete F.; Guarino, Maria P.; Yubero, Sara; Obeso, Ana; Conde, Silvia V.
Abstract : Key points: Leptin plays a role in the control of breathing, acting mainly on central nervous system; however, leptin receptors have been recently shown to be expressed in the carotid body (CB), and this finding suggests a physiological role for leptin in the regulation of CB function. Leptin increases minute ventilation in both basal and hypoxic conditions in rats. It increases the frequency of carotid sinus nerve discharge in basal conditions, as well as the release of adenosine from the CB. However, in a metabolic syndrome animal model, the effects of leptin in ventilatory control, carotid sinus nerve activity and adenosine release by the CB are blunted. Although leptin may be involved in triggering CB overactivation in initial stages of obesity and dysmetabolism, resistance to leptin signalling and blunting of responses develops in metabolic syndrome animal models. Abstract: Leptin plays a role in the control of breathing, acting mainly on central nervous system structures. Leptin receptors are expressed in the carotid body (CB) and this finding has been associated with a putative physiological role of leptin in the regulation of CB function. Since, the CBs are implicated in energy metabolism, here we tested the effects of different concentrations of leptin administration on ventilatory parameters and on carotid sinus nerve (CSN) activity in control and high‐fat (HF) diet fed rats, in order to clarify the role of leptin in ventilation control in metabolic disease states. We also investigated the expression of leptin receptors and the neurotransmitters involved in leptin signalling in the CBs. We found that in non‐disease conditions, leptin increases minute ventilation in both basal and hypoxic conditions. However, in the HF model, the effect of leptin in ventilatory control is blunted. We also observed that HF rats display an increased frequency of CSN discharge in basal conditions that is not altered by leptin, in contrast to what is observed in control animals. Leptin did not modify intracellular Ca 2+ in CB chemoreceptor cells, but it produced an increase in the release of adenosine from the whole CB. We conclude that CBs represent an important target for leptin signalling, not only to coordinate peripheral ventilatory chemoreflexive drive, but probably also to modulate metabolic variables. We also concluded that leptin signalling is mediated by adenosine release and that HF diets blunt leptin responses in the CB, compromising ventilatory adaptation. Key points: Leptin plays a role in the control of breathing, acting mainly on central nervous system; however, leptin receptors have been recently shown to be expressed in the carotid body (CB), and this finding suggests a physiological role for leptin in the regulation of CB function. Leptin increases minute ventilation in both basal and hypoxic conditions in rats. It increases the frequency of carotid sinus nerve discharge in basal conditions, as well as the release of adenosine from the CB. However, in a metabolic syndrome animal model, the effects of leptin in ventilatory control, carotid sinus nerve activity and adenosine release by the CB are blunted. Although leptin may be involved in triggering CB overactivation in initial stages of obesity and dysmetabolism, resistance to leptin signalling and blunting of responses develops in metabolic syndrome animal models.